Nanosuspension: Formulation, Charcterization and Evaluation - SHIVANAND PANDEY,; VIRAL DEVMURARI,; MANISH GOYANI,; HETAL ASHAPURI, (International Journal of Pharma and Bio Sciences, 2010)
Disperse system of solid-in-liquid or solid-in-semisolid, the dispersed phase comprising pure active compound or an active compound mixture. The average diameter of the dispersed phase is between 10 nm and 1,000 nm (determined by photon correlation spectroscopy), the distribution of the population being quite narrow, that is to say the proportion of microparticles in the particle population is very low. The nanosuspension can be surfactant-free, but can also comprise surfactants or stabilizers or both. The nanosuspension can also be lyophilized or spray dried, and the nanoparticles of a nanosuspension can also be incorporated into a solid carrier matrix. They form a depot where injected and slowely release the drug to the systemic circulation control manner. By using various polymers it can work as sustained release of numbers of drugs.